Assuring data quality in investigator-initiated trials in dutch hospitals: Balancing between mentoring and monitoring. (17th November 2022) - van Oijen, Jacqueline C.F.; Grit, Kor J.; Bos, Willem Jan W.; Bal, Roland
ABSTRACT: The complexity of regulations governing investigator-initiated trials (IITs) places a great burden on hospitals. Consequently, many hospitals seek to alleviate regulatory pressures by seeking an alternative quality management system (QMS). This paper takes the Netherlands as a case. To investigate how QMSs for IITs are organized in Dutch hospitals, we adopted the theoretical concepts of mentoring and monitoring in a mixed methods study in the period 2014–2018. In clinical practice and international guidelines, monitoring is seen as the standard quality assurance for ongoing trials. However, hospitals have implemented monitoring programs that resemble mentoring. The contrast between these ideal types is less pronounced in practice as both combine elements of compliance and feedback for learning in practice. In a monitoring setting, learning is one-way, from monitor to researcher; whereas mentoring focuses on mutual support and learning. To tackle problems in each system, the authority of the Board of Directors (BoD) and the BoD's relationship with staff members are crucial. We discuss the challenges that BoD and staff face in keeping an integrated view of the various components of QMSs.